Future chartered accountants' experience in the Malaysian audit firms: a focus on mentoring supports - Mohd Nor, Azleen Shabrina; Abu Kasim, Nor Aziah; Ismail, Hashanah; Mustapha, Mazlina (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Mentoring in the workplace has become a demanding need in the accounting professions. Good mentoring support will improve the future chartered accountants’ competencies. The International Federation of Accountants (IFAC) acknowledges the importance of mentoring supports by enforcing formal mentoring to IFAC member bodies, including the Malaysian Institute of Accountants (MIA). In Malaysia, there is little investigation on how future chartered accountants obtain mentoring supports throughout their working experience, particularly in the audit firms. Therefore, the objective of this study is to investigate the Malaysian chartered accountants’ experience in obtaining mentoring supports namely career and psychological supports, using the lens of mentoring theory. Interviews with eight future chartered accountants in Malaysia, who are currently undertaking the three years working experience to qualify as chartered accountants. The interviews were transcribed, coded and categorized into themes. The findings show that the process of mentoring supports are contextual to the number of chartered accountants in the workplace, workplace mentor-mentee initiative, career and psychosocial supports and peer mentoring. Although this study has a small sample, it is able to provide the understanding on the mentoring supports obtained by future chartered accountants in the big four and non-big four audit firms. This study makes two contributions: the enhancement of knowledge on mentoring and can assist policy makers in monitoring the mentoring supports obtained by the Malaysian future chartered accountants throughout their working experience.